Hidrólise e separação de peptídeos de buttermilk obtidos a partir de um biorreator a membrana - Fortuna, Sandrini Slongo (2020)
From the process that culminates the production of butter from the cream, buttermilk, buttermik, is also released, also considered as a by-product and even an industrial residue, as it does not present adequate reuse. This by-product contains water-soluble components of the cream, such as proteins, lactose and minerals. Particularly proteins, when reduced to peptides by enzymatic hydrolysis, have biological activity. This work aimed to obtain low molecular weight peptides from buttermik through a combined process of enzymatic hydrolysis and membrane filtration. The buttermilk was centrifuged and characterized for fat, protein, lactose, casein, total solids and pH, afterwards, it was subjected to hydrolysis with different commercial enzymes. The best enzyme was selected and submitted to the membrane bioreactor. Selected samples were lyophilized. In order to characterize the peptides formed after this step, analyzes of the calculation of the average chain length and the average molecular weight of the peptides and gel electrophoresis were performed. To assess bioactivity, analyzes of antimicrobial and antioxidant activity were performed. The enzymes showed different degrees of hydrolysis (GH), where Alcalase (endopeptidase) and Neutrase (exopeptidase) when used in sequence, showed better action reaching a GH of 34%. The centrifugation process was eliminated showing that there are no variations in the flow with or without its application. Rejection values were found R = 87.55% for the assay not using the hydrolysis process, and R = 60.25% for the assay using the hydrolysis process, proving that the hydrolysis made it possible for more protein to pass through the permeate, indicating process efficiency. The hydrolyzed samples showed bioactivity, with emphasis on the permeate obtained by membrane filtration and concentrate by lyophilization, which showed greater antioxidant activity. It was possible to combine the obtaining of a protein hydrolyzate, proving its bioactivity, with the reuse of a by-product little valued in the food industry.